Neuropsychological functioning and suicidal behaviours in patients with first-episode psychosis: A systematic review - Sánchez-Gutiérrez, Teresa; Barbeito, Sara; Gómez-Juncal, Rocío; Rodríguez-Ortega, Elisa; Becerra-García, Juan Antonio; Calvo, Ana (Acta Psychiatrica Scandinavica, 2023)
Introduction: Suicidal behaviour is particularly frequent in patients with psychosis. Therefore, prevention is a key objective of mental health policies. The aim of the current work is to systematically review the association between neurocognitive functioning and suicidal behaviour in patients with first-episode psychosis (FEP). Material and Methods: Of the 3051 studies reviewed, only 7 met the inclusion criteria. Documents in English from their earliest date of coverage until January 2022 were searched for in the following databases: PubMed, Science Direct, Web of Science, Cochrane Library, PsycINFO (ProQuest), and Springerlink. We used the PICO strategy to collect and categorize the data from each selected manuscript. Results: Overall, the results showed that the risk of suicidal behaviour is higher for FEP patients in the presence of a number of factors: poorer general neuropsychological functioning (except for working memory), poorer social cognition, more depressive symptoms, longer duration of untreated psychosis, higher awareness of the illness, poorer premorbid adjustment, and more frequent cannabis use. Discussion: Comprehensive general neuropsychology and assessment of social cognition, together with routine clinical record keeping, may help to identify FEP patients at a greater risk of attempting suicide.
Keywords: first-episode psychosis; neuropsychology; social cognition; suicide; suicide attempts; Scopus; JCR